Characterization of Extracted Lipid Obtained from Subcritical Water Extraction of Wet Algae for Biodiesel Production - Sitthithanaboon, W.; Punsuvon, V.; Vaithanomsat, P. (Asian Journal of Chemistry, 2015)
In this research, subcritical water at 200 °C for 0.5 h was shown to improve the efficiency for lipid extraction from wet algae Nannochloropsis gaditana (80 % moisture content), compared to the conventional solvent extraction method. Scanning electron microscopy was used to confirm the algae cell collapsed after extraction. The composition of extracted lipid was analyzed by gas chromatography. Fourier transform infrared spectroscopy, 1H NMR and 13C NMR spectroscopy were also conducted to study the properties of extracted lipid. The predominant fatty acids of algae lipid were shown to be palmitic acid (37.35-38.48 %), palmitoleic acid (28.54-32.85 %) and oleic acid (14.24-11.18 %). The 56.61 % wt. of free fatty acid was also detected. These properties indicated the possibility of extracted lipid as raw material for biodiesel production via two steps of reaction (esterification and transesterification).